The creative thinking handbook : your step-by-step guide to problem solving in business - Griffiths, Chris; Costi, Melina; Medlicott, Caragh (Kogan Page, London, 2022)
The Creative Thinking Handbook provides the correct application for creative thinking and action, by offering clear, practical tools and strategies so that you can develop creative thinking skills and help find brilliant solutions for any professional challenge. Based on research and proven-to-work creative thinking models, Chris Griffiths and Melina Costi present a clear introduction to what creative thinking is, explain why we all need to do it and will help you generate ideas and make better decisions. The Creative Thinking Handbook gets you to think differently by thinking creatively.
index
Keywords: Creative ability in business; Creative thinking; Problem solving